Analysis of Judge’s Decision on Registration of Trademark with The Same Naming (Study of Supreme Court Decision Number 640 K/Pdt.Sus-HKI/2020) - Silaban, Kenjiro; Anggriany, Fivienrencya; Gunawan, Freddy (Universitas Medan Area, 2024)
This article aims to evaluate the judge's ruling about the namesake trademark. Two parties that registered the SAMGONG trademark through DJKI are at the focal point of the issue. This article's articulation of the problem serves as an argument for the Panel of Judges' discussion of the legal implications and considerations surrounding the decision rendered by the Supreme Court in Number 640 K/Pdt.Sus-HKI/2020. This article concludes that a trademark is an asset that is legally protected and has economic worth from a commercial standpoint. Indonesia uses a first-to-file system, meaning that as soon as a trademark is registered in its home country, its owners acquire the rights to it. The Panel of Judges noted in their ruling that the Plaintiff originally registered its trademark in its own nation in 2008. That the Defendant's trademark registration is suspected of being done in bad faith because the Plaintiff's trademark has been sold and promoted internationally, making it a well-known trademark. Additionally, the DJKI was ordered to remove the Defendant's trademark from the General Register of Trademarks due to similarities in the naming of the trademarks owned by both parties. As a guardian of intellectual property, DJKI needs to be more cautious when examining trademarks registrations to check for essential similarities, particularly in trademark names.